Pengaruh Financial Leverage dan Profitabilitas Terhadap Penggelapan Pajak dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Wahyu; Suyanto (Jurnal Literasi Akuntansi, 2024)
Purpose: This study aims to determine: (1) To prove whether there is a positive influence of financial leverage on tax evasion, (2) To prove whether there is a positive influence of profitability on tax evasion, (3) To prove whether company size can strengthen the positive influence of financial leverage on tax evasion, (4) To prove whether company size can strengthen the positive influence of profitability on tax evasion. Method: This type of research is quantitative research using the document method. Samples were taken using purposive sampling technique. The sample consisted of 72 data from 13 property and real estate companies listed on the Indonesian stock exchange 2016-2022. The data analysis technique used is quantitative analysis using SPSS 21.0. Finding: Based on the research results, it shows that financial leverage has an effect on tax evasion, profitability has an effect on tax evasion, company size has an effect on tax evasion